Landscape variables influence over active restoration strategies of Nothofagus forests degraded by invasive Castor canadensis in Tierra del Fuego - Martinez Pastur, Guillermo José; Cellini, Juan Manuel; Lencinas, María Vanessa; Rosas, Yamina Micaela; Henn, Jonathan J.; Peri, Pablo Luis (MDPI, 2021)
North American beavers (Castor canadensis) are responsible for the major changes in the Tierra del Fuego Archipelago, altering riparian forests for the long-term. Passive restoration of the areas affected was ineffective in the medium-term (up to 20 years), being necessary active strategies. Plantations in abandoned ponds were made with Nothofagus pumilio and N. antarctica tree species across Tierra del Fuego island (Argentina). In the first experiment, we analysed the influence of biotic and abiotic factors in three micro-habitats in the impacted areas: front and tail of ponds, and cut not-flooded forest areas. Five-years-old N. pumilio seedlings had 39% survival in front, 21% in tails, and 46% in cut areas at year-3 of the restoration experiments, being negatively influenced by plant cover and soil moisture. Lower growth was recorded during year-1 (0.7–0.9 cm yr−1), but increased on time (1.9 cm yr−1 front, 1.6 cm yr−1 tail, 4.3 cm yr−1 cut areas). A second experiment explores the alternative to substitute the tree species to face the harder conditions of the impact and climate change. For this, we conducted a new plantation at four locations across the main bioclimatic zones, where 10–40 cm N. antarctica plants attained 17% survival in meadows (front and tail) and 30% in cut areas, being higher with larger than smaller plants (25% vs. 18%), and where they are mainly influenced by rainfall (4% in sites <400 mm yr−1 and 41% in >400 mm yr−1). The main damage was detected in the above-ground biomass due to dryness, but root survival allowed the emergence of new shoots in the following growing season. It is necessary to monitor different Nothofagus species across natural environments in the landscape to determine the feasibility and effectiveness of different strategies in restoration plans, considering the selection of climate-resilient tree species.